Enrichment of Bio-Active Phthalides in Celery Seed Oil - Halagur B. Sowbhagya; Pullabhatla Srinivas (Journal of Pharmacy and Nutrition Sciences, 2013)
Objective: To develop an efficient process to obtain a phthalide-enriched nutraceutical fraction from celery seed oil. Methods: Three approaches viz., fractional distillation, column chromatography and solvent-solvent partition, have been used. Results: Fractional distillation of celery seed oil (13.7g) afforded i) a limonene-rich fraction (7.6g, 97% purity), ii) a fraction containing β-selinene (2.8 g, 90 % purity) and iii) one containing phthalides (2.9 g, 90 % purity). Solvent-solvent partition of celery seed oil gave limonene (87%) and a fraction containing phthalides (49%), which on further fractionation afforded a phthalide-enriched fraction (90%). By conventional silica gel column chromatography, a product rich in phthalides (53-74%) could be obtained. Conclusion: Fractional distillation is shown to be a viable method to process celery seed oil into a phthalide-enriched product with high nutraceutical potential.